Pathogenesis of mice-adapted dengue virus in adult mice infection model / Tam Kim Kee - Tam, Kim Kee (2006)
The present study aims to study the pathogenesis of mice-adapted dengue type 2 virus (DENV-2MA) in an adult mice model towards the development of a potential animal model for dengue. This was performed by first adapting DENY- 2 in suckling mice brain, determining the virus viraemia phase and virus tropism in the infected adult mice, and evaluating specific immune response of the infected mice against the DENY-2MA and un"d" apted dengue virus type 2 (DENY- \ 2uA)· For the adaptation of DENV-2 in suckling mice brain, DENY-2 was inoculated into 1 day old suckling mice brain and harvested at day 7 postinfection (p.i). This was repeated three times prior to inoculation of the DENV-2MA into adult mice. Adult BALB/c mice (4 to 5 weeks) were infected intraperitoneally with 1.0 x 103 foci forming unit (Ifu) D ... NV-2MA or D NV-2u to study the virus replication in adult mice. Our finding showed that no iraemia phase was detected in these BALB/c mice. DENV-2MA, however, was r co ered from the infected mice brain and spleen. Study on the DENV-2MA and D NV- 2uA infected mice immune response showed that both DENY-2MA and D NV-2u were able to elicit primary immune response and anarnne tic re pon e in mice. The mice group that were inoculated with DENY-2MA and challenged with DENV-2uA gave the highest IgG level in comparison to other mice group . Our results revealed that DENV-2MA replicates better and elicits better immun response in adult BALB/c mice when compared with D NV-2u . The D NV- 2MA, hence, makes a more uitable candidate for the tud of D NV infe tion in II adult mice and ought to be used for future development of an animal model for DENY infection.